Ditch‐Structured Sulfur Cathode: Enhancing the Uniformity of Sulfur Redox Reaction in a Thick Sulfur Electrode. Issue 9 (26th March 2021) - Lee, Jinhong; Kwack, Hobeom; Kyung Kim, Min; Jo, Wonhee; Noh, Hyungjun; Kim, Yun‐Jung; Chu, Hyunwon; Baek, Jaewon; Roh, Youngil; Noh, Jiwhan; Kim, Hee‐Tak
Abstract: Increasing of sulfur loading in a sulfur cathode is a direct approach to improve the energy density of lithium sulfur (Li−S) batteries. However, the inhomogeneous redox reaction in high‐sulfur loaded, thick electrodes presents a challenge. Here, we report that the sulfur utilization in thick sulfur cathodes can be enhanced by simply making ditches on the electrodes. A nanosecond‐pulse laser is used to carve the line‐ditch pattern on the surface of the sulfur cathode, without damaging the surface pore structure. The ditch structure can promote the transport of lithium ion into the deep interior of sulfur cathode, resulting in more uniform sulfur redox reaction. A ditch‐structured sulfur cathode with a sulfur loading of 7 mg ⋅ cm −2 shows seven times higher sulfur utilization at a high current of 5.2 mA ⋅ cm −2 compared with an unpatterned sulfur electrode. Simple laser patterning technology provides a platform to engineer a thick cathode of high performance. Abstract : Ditches architecture : A line‐ditch pattern on the surface of the sulfur cathode enables the facile Li‐ion transport into the electrode with high sulfur loading of 7 mg ⋅ cm −2 and high current density of 5.2 mA ⋅ cm −2 . The regular interval and uniform depth on micron‐scale structure resulted in more uniform Li2 S deposition and high sulfur utilization. Therefore, our geometric electrode structure design is important for limited mass transport in a thick S‐cathode.